2017
DOI: 10.5603/gp.a2017.0120
|View full text |Cite
|
Sign up to set email alerts
|

Maternal-fetal outcome associated with adolescent pregnancy in a tertiary referral center: a cross-sectional study

Abstract: Objectives: This study was conducted to compare pregnancy outcomes of early-middle adolescent, late adolescent and adult women. Material and methods:The study focused on early-middle adolescent (n = 145), late adolescent (n = 1655) and adult (n = 1585) women who gave birth during 2014 through 2017, utilizing data obtained from the Zeynep Kamil Women and Children's Health Training and Research Hospital. Pregnancy outcomes were determined according to the rates of pregnancy complications, including method of del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
(26 reference statements)
0
15
0
2
Order By: Relevance
“…Previous studies carried out in industrialized countries, like a Korea, Canada, Slovenia and Iran have revealed no excess risks of preeclampsia among adolescents [6], [10], [28], [42], whereas higher risks have been reported in developing countries, like a Turkey and Zambia [43], [44]. Our results do not support earlier findings of a higher risk of gestational hypertension and preeclampsia in teenage mother’s compared to adults [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies carried out in industrialized countries, like a Korea, Canada, Slovenia and Iran have revealed no excess risks of preeclampsia among adolescents [6], [10], [28], [42], whereas higher risks have been reported in developing countries, like a Turkey and Zambia [43], [44]. Our results do not support earlier findings of a higher risk of gestational hypertension and preeclampsia in teenage mother’s compared to adults [45].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we have found a decreased risk of the need for neonatal transfer in adolescents compared to adults. Other authors reported contradictory results [43]. Usynina A et al, (2018) reported for a higher rate of neonatal transfer to higher level hospital of adolescent women compared to adults (11.2% vs 9.8%, p = 0.042) [40].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of pregnancy among adolescents is increasing, especially in developing countries, with higher adverse health outcomes [3]. More than 11 percent of births globally were because of adolescent mothers [4, 5]. Previous studies have shown that adolescent pregnancy is associated with physical, social problems [2], and affects the economic status of girls, their families, and countries [2, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent pregnancies are a public health problem because of the negative consequences these pregnancies can have on maternal health [2]. Adolescent mothers have an increased risk of preeclampsia [3], inadequate gestational weight gain, [4], and height stunting [5] due to a nutrient competition between the mother and the fetus [6,7]. Maternal growth retardation has, in turn, been associated with adverse maternal and neonatal outcomes [8].…”
Section: Introductionmentioning
confidence: 99%